Analisis Perbedaan PSAK 1 Revisi 2013 dengan IAS 1 Tentang Penyajian Laporan Keuangan dan PSAK 3 Revisi 2016 dengan IAS 34 Tentang Laporan Keuangan Interim - M Fauzan Aziz; Elina Syafitri; M Luthfy Abdul K; Fajar Panji G; M Shafta Putra (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
An interim financial report is a financial report that includes complete financial statements as described in PSAK No. 1 but in an interim period, or a time span of less than one year. This study aims to explain the comparison of policies that regulate PSAK No. 3 in the preparation of interim financial statements. The method used in this paper is a literature study, where the author collects several relevant national and international journals as the main source for this writing. The results show that the difference between PSAK and IAS is not significantly different. This is due to various factors and conditions in Indonesia. This study reveals that (1) under the supervision of PSAK, IAS does not regulate capital market regulations. (2) PSAK 1 still approves the use of the word "balance sheet" and does not require the use of the word "financial statements". (3) IAS 1 does not apply to several entities, such as sharia entities and the public sector. (4) PSAK 1 which adopts IAS 1 requires the selection of other comprehensive income items before tax to show the amount of tax related to the two groups. (5) IAS 1 lists non-current assets followed by current assets. While in PSAK No. 1 is presented in reverse order. (6) PSAK 3 removes the policy regarding the effective date because it is considered irrelevant. (7) PSAK 3 doesn't adopt contractual changes or anticipate price changes that refer to the conceptual framework because it has not been reviewed by KDPPLK.